Site- and horizon-specific patterns of microbial community structure and enzyme activities in permafrost-affected soils of Greenland - Antje Gittel (Department of Biology, Centre for Geobiology, University of Bergen); Jiří Bárta (Department of Ecosystems Biology, University of South Bohemia); Iva Kohoutová (Department of Ecosystems Biology, University of South Bohemia); Jörg Schnecker (University of Vienna); Birgit Wild (University of Vienna); Petr Čapek (Department of Ecosystems Biology, University of South Bohemia); Christina Kaiser (University of Vienna); Vigdis L. Torsvik (Department of Biology, Centre for Geobiology, University of Bergen); Andreas Richter (University of Vienna); Christa Schleper (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna); Tim Urich (Department of Ecogenomics and Systems Biology, Faculty of Life Sciences, University of Vienna) (Frontiers in Microbiology, 2014)
The abstract is available here: https://uscholar.univie.ac.at/o:467107 The abstract is available here: https://uscholar.univie.ac.at/o:467107